PEMBELAJARAN ANSAMBEL MUSIK DI SMA NEGERI 1 PAINAN - Enggi Maihendra Ikhlas; Esy Maestro; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2018)
ABSTRACTThis study aims to describe the implementation of learning musical ensemble in 9th grade students of IIS 3 at SMA 1 Painan. This type of research is qualitative research that uses descriptive methods. The object of this study was the students of grade XI IIS 1, amount of students are 34 students who were attending cultural arts learning that contained music learning with music ensemble material at SMA 1 Painan.Based on the results of research, researcher found in the field, it can be explained that the learning of musical ensembles at SMA Negeri 1 Painan has an implementation process which is not in accordance with the lesson plan used by the teacher in the classroom. The incopability of the implementation in class room caused by several reasons expressed by the teacher, they are the Lesson Plan was made by other parties and lack of musical instruments at schools so students need to provide their own musical instruments. Even though, the result of learning in grade XI IIS 1 runs well. Students are taught to be able to arrange a simple musical ensembles independently. Students are also required to be able to work together and be active in groups to discuss and think creatively as the government's goals about character building for students. Keywords: Learning, Music ensemble